Brain Glycogen—Its Metabolic Role in Neuronal Health and Neurological Disorders—An Extensive Narrative Review - Ana Isabel Beltran-Velasco (Metabolites)
Background: Brain glycogen is imperative for neuronal health, as it supports energy demands and metabolic processes. This review examines the pathways involved in glycogen storage and utilization in the central nervous system, emphasizing their role in both physiology and pathology. It explores how alterations in glycogen metabolism contribute to neurological disorders, including neurodegenerative diseases, epilepsy, and metabolic conditions while highlighting the bidirectional interaction between neurons and glia in maintaining brain homeostasis. Methods: A comprehensive search of articles published between 2015 and 2025 was conducted using the following databases: ScienceDirect, Scopus, Wiley, Web of Science, Medline, and PubMed. The selection of relevant studies was based on their focus on brain glycogen metabolism and its role in neurological conditions, with studies that did not meet the inclusion criteria being excluded. Results: The metabolic processes of brain glycogen are subject to rigorous regulation by astrocyte–neuron interactions, thereby ensuring metabolic homeostasis and energy availability. The dysregulation of glycogen storage and mobilization has been implicated in the development of synaptic dysfunction, excitotoxicity, and neurodegeneration in a variety of disorders. For instance, aberrant glycogen accumulation in diseases such as Lafora disease has been associated with severe neurodegeneration, while impaired glycogen mobilization has been shown to exacerbate energy deficits in Alzheimer’s and epilepsy. Conclusions: Targeting brain glycogen metabolism represents a promising approach for therapeutic intervention in neurological disorders. However, the translation of these strategies to human models remains challenging, particularly with regard to the long-term safety and specificity of glycogen-targeted therapies.